2021
DOI: 10.1038/s41598-021-00725-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and antimicrobial susceptibility profiles during primary antimicrobial prophylaxis for pediatric acute myeloid leukemia

Abstract: Limited data are available on antimicrobials exposure and microbiology evolution in pediatric acute myeloid leukemia (AML) patients underwent antimicrobials prophylaxis. To assess the effectiveness of antimicrobials prophylaxis, antibiotic susceptibilities of bacteria, and exposure of antimicrobials during intensive chemotherapy for AML patients, 90 consecutive de novo AML patients aged 0–18 years between January 1, 1997 and March 31, 2018 were enrolled. Vancomycin, ciprofloxacin and voriconazole prophylaxis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In our study, musculoskeletal toxicities were not reported in any patient receiving ciprofloxacin prophylaxis, which was in agreement with two other studies on the efficacy of ciprofloxacin prophylaxis in childhood AML [16,18]. A few other retrospective studies among pediatric AML patients have shown that cefepime monotherapy [14] or vancomycin combined with an agent with Gram-negative coverage are highly effective in reducing bacterial BSIs [14,15,17,20,23]. However, vancomycin is associated with dosing difficulties and infusion-related side effects and requires administration (at least) every 12 h with therapeutic drug monitoring.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, musculoskeletal toxicities were not reported in any patient receiving ciprofloxacin prophylaxis, which was in agreement with two other studies on the efficacy of ciprofloxacin prophylaxis in childhood AML [16,18]. A few other retrospective studies among pediatric AML patients have shown that cefepime monotherapy [14] or vancomycin combined with an agent with Gram-negative coverage are highly effective in reducing bacterial BSIs [14,15,17,20,23]. However, vancomycin is associated with dosing difficulties and infusion-related side effects and requires administration (at least) every 12 h with therapeutic drug monitoring.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to daily dosing, such an alternate dosing schedule not only improves the quality of life but also minimizes the antibiotic exposure and handling of central venous lines. These advantages are of major interest as a decreased susceptibility to vancomycin and teicoplanin of Enterococcus species [23] and an increase in VRE strains in rectal cultures [15] have been observed with the use of vancomycin prophylaxis. One study also observed VRE BSIs with the use of vancomycin prophylaxis [15], whereas others did not [14,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 9 studies selected for the meta-analysis, 6 were retrospective single-center studies [ 33–38 ] and 3 were prospective studies [ 39–41 ], 2 of which were randomized [ 40 , 41 ]; 1 was also multicentric [ 41 ]. Two studies included only patients with acute lymphoblastic leukemia (ALL) [ 39 , 40 ], 1 only patients with acute myeloid leukemia (AML) [ 37 ], 2 both ALL and AML patients [ 33 , 42 ], 1 only patients undergoing autologous HSCT (auto-HSCT) [ 35 ], 2 both auto- and allogenic HSCT (allo-HSCT) [ 34 , 36 ], and 1 all groups of patients [ 41 ]. Two of the 6 studies on ALL patients studied relapsed ALL (rALL) [ 33 , 41 ].…”
Section: Resultsmentioning
confidence: 99%